RETRACTED: The influence of arts education on love of the natural environment - Komarovska Oksana; Vlasova Valeria; Pet'ko Lyudmila; Voloshenko Anna; Holinska Tetiana; Prodius Oksana (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001